Pore water geochemistry of sediment core GeoB24348-2 - Matthias Zabel; Silvana Pape; Gerhard Bohrmann; Nele Behrendt (PANGAEA, 2023)
The samples are retrieved from sediment core GeoB24348-2 (Brine pool; 0-537 cm) in the Olimpi mud volcano field, located south of Crete at the Mediterranean Ridge accretionary complex. Major and minor element concentrations were measured at MARUM by ICP-OES and Metrohm ion chromatography and on selected samples. On board, 5 to 10 ml of pore water were extracted from the splitted cores every 5 to 20 cm during using rhizon samplers. Cations (B; Ba; Ca; Fe; K; Li; Mg; Mn; Na; S; Si; Sr) were measured by ICP-OES (Agilent 710 Simultan with a precision of 1%) and anions (F; Cl; Br; SO4) were measured by Metrohm ion chromatography with a precision of <1%.